The Tube 3 Module Designed for Practicing Vesicourethral Anastomosis in a Virtual Reality Robotic Simulator: Determination of Face, Content, and Construct Validity - Kang, Sung Gu; Cho, Seok; Kang, Seok Ho; Haidar, Abdul Muhsin; Samavedi, Srinivas; Palmer, Kenneth J.; Patel, Vipul R.; Cheon, Jun (Urology (Ridgewood, N.J.), 2014)
To better use virtual reality robotic simulators and offer surgeons more practical exercises, we developed the Tube 3 module for practicing vesicourethral anastomosis (VUA), one of the most complex steps in the robot-assisted radical prostatectomy procedure. Herein, we describe the principle of the Tube 3 module and evaluate its face, content, and construct validity. Residents and attending surgeons participated in a prospective study approved by the institutional review board. We divided subjects into 2 groups, those with experience and novices. Each subject performed a simulated VUA using the Tube 3 module. A built-in scoring algorithm recorded the data from each performance. After completing the Tube 3 module exercise, each subject answered a questionnaire to provide data to be used for face and content validation. The novice group consisted of 10 residents. The experienced subjects (n = 10) had each previously performed at least 10 robotic surgeries. The experienced group outperformed the novice group in most variables, including task time, total score, total economy of motion, and number of instrument collisions (P <.05). Additionally, 80% of the experienced surgeons agreed that the module reflects the technical skills required to perform VUA and would be a useful training tool. We describe the Tube 3 module for practicing VUA, which showed excellent face, content, and construct validity. The task needs to be refined in the future to reflect VUA under real operating conditions, and concurrent and predictive validity studies are currently underway.